2009
DOI: 10.3899/jrheum.080657
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Ultrasonography in Early Diagnosis of Metatarsal Bone Stress Fractures: A Pilot Study of 37 Patients

Abstract: In cases of normal radiographs, US is indicated in the diagnosis of metatarsal bone stress fractures, as it is a low cost, noninvasive, rapid, and easy technique with good sensitivity and specificity. From these data, we propose a new imaging algorithm including US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 25 publications
2
113
0
1
Order By: Relevance
“…Although its chief application in musculoskeletal disorders is the assessment of soft tissues, US can help in detecting SF. Banal et al reported 70% sensitivity for US compared to an MRI for the examination of fractures of the second metatarsal [12]. Several studies have described ultrasonographic findings of SF (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…Although its chief application in musculoskeletal disorders is the assessment of soft tissues, US can help in detecting SF. Banal et al reported 70% sensitivity for US compared to an MRI for the examination of fractures of the second metatarsal [12]. Several studies have described ultrasonographic findings of SF (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…14 Since then, US has aided in diagnosing additional metatarsal stress fractures, 8,15,16 detection of other occult fractures in the foot and ankle, 17 stress fractures of the lower limb, 18 and prediction of fracture callus formation with the use of color Doppler US. 19 Furthermore, US has been recommended as a follow-up examination to negative radiography in the diagnostic workup of suspected stress fractures because it may circumvent the need for more costly tests such as MRI and skeletal scintigraphy.…”
Section: Figmentioning
confidence: 99%
“…19 Furthermore, US has been recommended as a follow-up examination to negative radiography in the diagnostic workup of suspected stress fractures because it may circumvent the need for more costly tests such as MRI and skeletal scintigraphy. 8,17 Currently, the following 5 US criteria are used to determine the presence of stress fractures: increased vascularity as demonstrated using color Doppler, periosteal elevation with a cortical break/loss of periosteal contiguity, periosteal reaction and early callus formation, hypoechoic area adjacent to the cortical break (corresponding to hematoma), and overlying soft tissue edema. 8,16,18 In this case, the following US criteria were initially noted: increased vascularity demonstrated with color Doppler, periosteal elevation, and cortical disruption.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations